2022
DOI: 10.3390/jcm11051337
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Vessel Density of the Macula in Preterm Children Using Optical Coherence Tomography Angiography

Abstract: Background: Retinal morphology changes may be associated with prematurity and can lead to visual impairment. Optical coherence tomography angiography may contribute to understanding the pathomechanism of structural and vascular retinal impairment in premature children. The aim of this study was to assess an influence of prematurity, neonatal clinical characteristics, and a history of retinopathy of prematurity (ROP) on the morphology and retinal vascularity of macula in children. Methods: A case–control study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
(97 reference statements)
2
7
0
Order By: Relevance
“…They also found the ROP group requiring treatment displayed significantly decreased whole VD and parafoveal VD in the SCP, and significantly increased foveal VD in the SCP in comparison to preterm infants without ROP. The ROP group not requiring treatment only displayed significantly increased foveal VD in the DCP versus preterm infants without ROP (Czeszyk et al., 2022). Contrarily, Lavric et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found the ROP group requiring treatment displayed significantly decreased whole VD and parafoveal VD in the SCP, and significantly increased foveal VD in the SCP in comparison to preterm infants without ROP. The ROP group not requiring treatment only displayed significantly increased foveal VD in the DCP versus preterm infants without ROP (Czeszyk et al., 2022). Contrarily, Lavric et al.…”
Section: Resultsmentioning
confidence: 99%
“…Vascular changes, as measured by OCTA, have also been investigated between ROP infants and preterm infants. Two studies have found that FAZ area was significantly smaller in ROP patients compared to preterm children (Czeszyk et al, 2022;Mataftsi et al, 2021). The study by Mataftsi et al further found that foveal VD in both the SCP and DCP was significantly higher in spontaneously regressed ROP patients in comparison to preterm patients (Mataftsi et al, 2021).…”
Section: Rop Versus Preterm Infantsmentioning
confidence: 93%
“…Evaluation of healthy children also differentiates their retinal structure from preterm children's retinas and several studies on the latter have come forward where a thinned GCC has been linked to prematurity and may be associated with their visual impairment (Czeszyk et al, 2022; Lee, Chang, et al, 2018; Ortueta‐Olartecoechea et al, 2021). However, the GCC is thicker in children with retinopathy of prematurity as noted in one study, and needs careful assessment and monitoring for glaucoma development in these children (Lee, Chang, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since ROP is a proliferative retinal vascular disease and Plus disease is characterized by vascular tortuosity and dilation, it is hypothesized that the vessel density in Plus disease is greater than that of a healthy retina. The density of retinal vessels has been extensively discussed in the academic literature as a potential indicator of ROP 32 36 , particularly in relation to Plus disease 35 . Therefore, in our study, we investigated the density of vessels as a potential indicator of Plus disease, in addition to evaluating tortuosity and dilation.…”
Section: Methodsmentioning
confidence: 99%